Acid and alkaline phosphatase in atretic follicles of buffalo ovary - KHERA, K S; BRAR, A S; GURAYA, S S (The Indian Journal of Animal Sciences, 2013)
Follicular fluid was aspirated from atretic follicles in ovaries collected from slaughterhouse and the concentration of acid and alkaline phosphatase measured. Acid phosphatase activities did not differ significantly in different sizes of atretic follicles while that of alkaline phosphatase was higher and increased with follicular size. JIigh concentration of alkaline phosphatase may be a characteristic of atresia in large atrelic follicles.